1169Impact of sex-specific growth centiles in utero - a statewide population cohort study. (2nd September 2021) - Pritchard, Natasha; Walker, Susan; Tong, Stephen; Lindquist, Anthea
Abstract: Background: Sex impacts birthweight, with male babies heavier on average. However, growth charts in pregnancy are often sex-neutral. Small babies (<10 th centile) are at risk of adverse outcomes. We aimed to identify the impact of using sex-specific charts during pregnancy, and if this detected more babies at risk of stillbirth. Methods: Retrospective cohort study including all infants born in Victoria from 2005-2015 (n = 529, 261). We applied the same growth centiles, either adjusted or not adjusted for fetal sex. We compared overall <10 th centile populations, populations of males considered small by sex-specific charts only, and populations of females considered small by sex-neutral charts only. Stillbirth risk was our primary outcome. Results: Of those <10 th centile by sex-neutral charts, 39.6% were male and 60.5% female, but using sex-specific charts, 50.3% were male and 49.7% female. 19.2% of < 10 th centile females were reclassified as > 10 th centile using sex-specific charts. These females were not at increased risk of stillbirth or adverse outcomes compared with a healthy weight infant, but were at greater risk of being delivered by obstetricians on suspicion of growth restriction. A further 25.0% of male infants were reclassified as < 10 th centile by sex-specific charts. These male newborns, compared to a healthy weight baby, were at greater risk of stillbirth (RR 1.94, 95%CI 1.30-2.90) and other adverse outcomes. Conclusions: Use of growth centiles not adjusted for fetal sex disproportionately classifies female infants as < 10 th centile, increasing their risk of unnecessary intervention, and fails to identify a cohort of male infants at increased risk of adverse outcomes, including stillbirth. Key messages: Male babies are heavier than female babies. Thus, ultrasound charts growth charts should be sex-specific.